2020
DOI: 10.3390/ijerph17113782
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cadmium Toxicity

Abstract: Cadmium (Cd) is a toxic non-essential transition metal that poses a health risk for both humans and animals. It is naturally occurring in the environment as a pollutant that is derived from agricultural and industrial sources. Exposure to cadmium primarily occurs through the ingestion of contaminated food and water and, to a significant extent, through inhalation and cigarette smoking. Cadmium accumulates in plants and animals with a long half-life of about 25–30 years. Epidemiological data suggest that occupa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
772
2
24

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,605 publications
(806 citation statements)
references
References 142 publications
8
772
2
24
Order By: Relevance
“…Meanwhile, the demethylase KDM5B mRNA level was significantly changed by MC-LR exposure, indicating that MC-LR meiotic maturation failure may result from an impairment of epigenetic modifications in porcine oocytes. These results consistent with the opinion which indicated that pollutants might cause cell dysfunctions via epigenetic modifications ( Genchi et al, 2020 ; Zheng et al, 2020 ). However, VC restored these abnormal epigenetic alterations in MC-LR-exposed oocytes.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, the demethylase KDM5B mRNA level was significantly changed by MC-LR exposure, indicating that MC-LR meiotic maturation failure may result from an impairment of epigenetic modifications in porcine oocytes. These results consistent with the opinion which indicated that pollutants might cause cell dysfunctions via epigenetic modifications ( Genchi et al, 2020 ; Zheng et al, 2020 ). However, VC restored these abnormal epigenetic alterations in MC-LR-exposed oocytes.…”
Section: Discussionsupporting
confidence: 92%
“…For example, Cd exposure influences the human male reproductive organs/system and deteriorates spermatogenesis and semen quality, especially sperm motility and hormonal synthesis/release. Based on experimental and human studies, it also impairs female reproduction and the reproductive hormonal balance and affects menstrual cycles [ 16 , 17 ]. In animals, experimental studies revealed that Cd and Cd compounds (referred to as Cd) by multiple routes of exposure prompt benign and malignant tumor formation at various sites in many species of experimental animals [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that the heavy metals cadmium and lead interfere with a number of functions of the erythropoietic system, the processes that make red blood cells. In addition, both cadmium and lead are highly bound to intracellular and membrane proteins in the red blood cell [ 1 , 2 ], complicating analysis of their effects on erythropoiesis. Both metals are also toxic to the kidney [ 3 ], which is the site of erythropoietin synthesis, the primary hormone that stimulates red blood cell generation in the bone marrow [ 4 ].…”
Section: Introductionmentioning
confidence: 99%